A bibliometric analysis of biochar application in wastewater treatment from 2000 to 2021 - Nan, H.; Wang, L.; Luo, D.; Zhang, Y.; Liu, G.; Wang, C. (International journal of environmental science and technology (Tehran), 2023)
Biochar, a carbon-rich porous material derived from biomass, receives increasing attention and interests in recent years. Research development of biochar-related topic is rarely reported at macroscopic perspective. This work gives an overview of biochar application in wastewater treatment based on bibliometric analysis. 2196 articles related to the topic were collected from Web of Science database with period of 2000–2021. The publications were examined using bibliometric tools of Bibliometrix package, CiteSpace, and VOSviewer. Publications output, subject categories, journals authors, institutions, and countries were analyzed. Detailed analysis of keywords from perspectives of co-occurrence network, keyword clusters, citation bursts, and Sankey diagram was conducted. A rapid development of researches on the topic is observed in the past 5 years, and the annual publications increase sharply from 109 in 2016 to 698 in 2021. The leading subject category is Environmental Science, and the journal of Environmental Science and Pollution Research publishes the most articles. The most productive country, institution, and author are China, Chinese Academy of Sciences, and Yong Sik Ok from Korea University, respectively. There exists close cooperation between countries and researchers. The fabrication of functional biochar and contaminant removal from wastewater via adsorption and catalytic degradation have been widely studied. The preparation of functional biochar, the development of techniques, and the in-depth understanding or contaminant removal are research trends. This work provides an overview of wastewater treatment associated with biochar, and offers insights into the research development and future trends.